Method for preparing PZT target material for magnetron sputtering by using spark plasma sintering method
Through SPS technology, the discharge plasma sintering method is adopted, and the problems of high energy consumption, low production efficiency and environmental pollution in traditional solid-phase sintering methods are solved, and the preparation of PZT targets with low temperature rapid sintering, low energy consumption, high density and high performance are achieved.
Patent Information
- Application Number
- CN202510203709.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-11
AI Technical Summary
The traditional solid-phase sintering method sinters PZT targets at high temperatures, resulting in high energy consumption, low production efficiency, excessive grain growth, and easy evaporation of lead oxide, causing environmental pollution.
The discharge plasma sintering method (SPS technology) is used to heat the material by generating discharge phenomena inside the sample through pulsed current, achieving rapid sintering. The method includes steps such as raw material mixing, ball milling, pre-firing, hot-pressed powder preparation, vacuum pressurized sintering, annealing and polishing.
It achieves a low sintering temperature, short sintering time, low energy consumption and fast densification speed, which reduces the volatility of lead oxide, reduces the pollution to the environment, and improves the density and performance of the material.
Smart Images

Figure CN119797912A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric material preparation, and in particular to a method for preparing a PZT target material for magnetron sputtering by utilizing a discharge plasma sintering method. Background Art
[0002] The preparation of piezoelectric ceramic Pzt targets generally adopts the traditional solid-phase sintering method. The temperature for sintering piezoelectric ceramics into porcelain is as high as 1200℃, and it is kept warm for 2 to 4 hours. The melting point of lead oxide is about 900℃. Lead oxide itself is a toxic chemical. Therefore, although the traditional solid-phase sintering method is simple to operate and only needs to be sintered in a muffle furnace, the temperature is much higher than the melting point of lead oxide, which will cause the Pb element to volatilize, causing great harm to both the experimenters and the environment.
[0003] The patent application for a high-density PZT target material and its preparation method (patent number CN201710679330.1, publication number: CN107445617A) adopts the traditional solid phase method to prepare the PZT target material: after ball milling the mixed slurry of deionized water, dispersant and PZT porcelain, a binder is added, injected into the mold, demolded, and the obtained green body sample is dried to obtain a green body with a relative density greater than 50%; after the green body is debinded, it is lead-embedded sintered; its production process is simple, easy to operate and control, low production cost, and high production efficiency, but the sintering temperature it adopts is too high, the insulation time is too long, resulting in a large amount of energy consumption, low production efficiency, and it is also easy to cause excessive grain growth, thereby affecting the performance. During the heating process of the muffle furnace, since heating and pressurization cannot be carried out at the same time, the density has not yet reached a higher requirement. At the same time, the use of lead-embedded technology for sintering will cause environmental pollution and fail to meet the requirements of green environmental protection. Summary of the invention
[0004] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a PZT target material for magnetron sputtering by using a spark plasma sintering method. First, the raw materials of the piezoelectric ceramic are mixed in proportion, and pre-sintered after mechanical treatment such as ball milling to remove impurities and organic matter. Then, after granulation and tableting, final sintering is performed to obtain a PZT piezoelectric ceramic target material that can be used for magnetron sputtering. The method has the advantages of low sintering temperature, short sintering time, low energy consumption, and fast densification speed.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A PZT target material for magnetron sputtering, with a molecular formula of PbZr(0.48-0.52)Ti(0.48-0.52).
[0007] A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, specifically comprising the following steps:
[0008] Step 1. According to the molar mass ratio of the raw material components chemical formula Pb3O4: ZrO2: TiO2 = 685.6: (59.1456-64.0744): (38.3376-41.5324), take the raw materials and mix them evenly to obtain a mixed powder;
[0009] Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, ball mill for 8 to 12 hours and dry to obtain dried powder;
[0010] Step 3. Pre-sinter the dried powder obtained in step 2 at a temperature of 800 to 900° C. for 3 to 5 hours to form a powder of the main crystal phase of PZT;
[0011] Step 4. Grind the powder of the PZT main crystal phase formed after pre-sintering in step 3 at room temperature for 10 to 60 minutes, pass through a 60 to 100 mesh sieve, and take the powder with a particle size of less than 0.150 mm as hot pressing powder;
[0012] Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the sps device, apply a pressure of 5 to 10 MPa to pre-press and compact it to obtain a pre-pressed block;
[0013] Step 6. Place the block obtained in step 5 in an SPS device for pressure sintering in a vacuum environment to obtain a semi-finished target material;
[0014] Step 7. Annealing the semi-finished target material obtained in step 6;
[0015] Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it with an automatic polishing machine until the surface is smooth; wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; finally, dry it at 80-120°C for 2-6 hours.
[0016] In the step 2, the mass ratio of powder: anhydrous ethanol: grinding balls is 1: (2-5): (2-5).
[0017] The vacuum degree of the vacuum environment in step 6 is 5*(10 -2 ~10 -1 ), the sintering temperature of pressure sintering is 800-1000°C, the holding pressure is 20-30MPa, and the pressure holding sintering time is 8-15min.
[0018] The annealing treatment in step 7 is carried out in an atmospheric environment, with an annealing temperature of 700 to 900° C. and an annealing time of 8 to 10 hours.
[0019] The semi-finished target material processed in step 8 is connected to the target material back plate by using conductive adhesive to complete the preparation of the PZT target material.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. Fast heating rate: The present invention adopts spark plasma sintering (SPS) technology to heat the material through the discharge phenomenon generated by pulse current inside the sample, which plays a role in rapid sintering. Compared with traditional solid phase sintering, the SPS heating rate is an order of magnitude faster than muffle furnace heating, which is 10 times faster.
[0022] 2. Low sintering temperature: The present invention adopts spark plasma sintering SPS technology, which can be sintered in a vacuum environment, and the melting point of lead oxide in the material is about 900°C. Due to the low oxygen concentration in the vacuum environment, the driving force for the conversion of lead oxide into Pb and oxygen is reduced. The SPS technology reduces the volatilization of lead oxide, and has the advantage of a sintering temperature that is about 200 to 500°C lower than that of traditional solid phase sintering.
[0023] 3. Short insulation time: The present invention adopts spark plasma sintering (SPS) technology, which can make the sample accompanied by pressure assistance during sintering, which is helpful for rapid densification and control of grain growth, and has the benefit of rapid sintering.
[0024] 4. Low energy consumption: The present invention adopts spark plasma sintering (SPS) technology. Because it uses pulse current to directly energize the sample, the entire sintering process is very rapid, and the low-temperature sintering and heat preservation time are greatly reduced. Compared with traditional solid phase sintering, it greatly reduces energy consumption and has the benefit of more energy saving.
[0025] 5. Rapid densification: The present invention adopts spark plasma sintering (SPS) technology to generate uniform Joule heat between powder particles through pulse current, so that all parts inside the material are evenly heated, avoiding the temperature gradient problem commonly seen in traditional sintering. In this system, ceramics with a relative density of more than 98% can be obtained by sintering at 800°C to 1000°C for only 8 to 10 minutes. It can achieve rapid densification of materials at lower temperatures, help retain finer grains, and thus improve the performance of the material.
[0026] 6. Good applicability: The present invention adopts the spark plasma sintering SPS technology. SPS can easily sinter metal compounds with high melting point and high hardness, and can also quickly sinter nanomaterials at low temperature while maintaining their nanoscale grain size. SPS technology can sinter parts with complex shapes and gradient functional materials (FGM). Materials with gradient composition changes are prepared in one sintering process. SPS can achieve low-temperature rapid sintering through self-heating and surface activation between particles, thereby effectively processing high melting point and brittle metal compounds. The overall application scenarios are very rich.
[0027] 7. Environmental friendliness: The present invention adopts spark plasma sintering SPS technology, which plays an environmental protection role in the experimental system. Since the sintering temperature is not as high as that of the traditional sintering method, the volatilization of Pb can be reduced to a great extent, which has the benefits of reducing damage to experimenters and the environment and being green and environmentally friendly.
[0028] In summary, compared with the prior art, the present invention has the advantages of low sintering temperature, short sintering time, low energy consumption and fast densification speed. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The experimental flow chart of the present invention.
[0030] Figure 2 XRD spectra of the PZT targets prepared in Examples 1 to 5 of the present invention; there are no impure peaks and other impurity phases in the graphs.
[0031] Figure 3 These are photos of the target material surface before annealing in Example 1 of the present invention, wherein (a) is a front photo of the target material, and (b) is a photo of measuring the diameter of the target material.
[0032] Figure 4 These are photos of the target surface after annealing in Example 1 of the present invention, where (a) is a photo for determining the target annealing parameters, and (b) is an enlarged photo of the target after annealing; after annealing, the PZT target shows its normal color.
[0033] Figure 5 These are photos of the target material before and after machining according to Example 1 of the present invention, wherein (a) is a photo of the annealed target material before machining, and (b) is a photo of the annealed target material after machining.
[0034] Figure 6 These are SEM photos of the target material taken after machining in Example 1 of the present invention, including (a) 1500 times, (b) 2500 times, (c) 4000 times, (d) 5000 times, and (e) 7000 times. The grains are relatively small as a whole, and the grains are not grown by rapid sintering.
[0035] Figure 7 This is a photo of the back side of the target material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] A method for preparing a PZT target for magnetron sputtering by spark plasma sintering, see Figure 1 , specifically including the following steps:
[0039] Step 1. According to the chemical formula of the raw material components, the molar mass ratio is Pb3O4: ZrO2: TiO2 = 685.6: 59.1456: 41.5324, molecular formula: Pb(Zr 0.48 Ti 0.52 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder;
[0040] Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, with the mass ratio of powder: anhydrous ethanol: grinding balls being 1:3:2, and ball milling for 12 hours and drying to obtain dried powder;
[0041] Step 3. Place the dried powder obtained in step 2 into a muffle furnace for pre-sintering at a temperature of 900° C. for 4 hours to form a powder of the main crystal phase of PZT;
[0042] Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT (near the morphotropic phase boundary MPB) at room temperature for 30 minutes, pass through 60-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder;
[0043] Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 7Mpa to pre-press and compact it to obtain a pre-pressed block;
[0044] Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -2 The target material is subjected to pressure sintering at a sintering temperature of 920°C, a holding pressure of 30 MPa, and a holding pressure sintering time of 10 min to obtain a semi-finished target material.
[0045] Step 7. Annealing the semi-finished target obtained in step 6, in an atmospheric environment, at an annealing temperature of 700° C., for 8 hours;
[0046] Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it with an automatic polishing machine; polish until the surface is smooth, wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; finally dry at 100°C for 4 hours.
[0047] The semi-finished target material processed in step 8 is connected to the target material back plate by using conductive adhesive to complete the preparation of the PZT target material.
[0048] Example 2
[0049] A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, specifically comprising the following steps:
[0050] Step 1. According to the chemical formula of the raw material components, the molar mass ratio is Pb3O4:ZrO2:TiO2=685.6:61.61:39.935, molecular formula: Pb(Zr 0.5 Ti 0.5 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder;
[0051] Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, the mass ratio of powder: anhydrous ethanol: grinding balls is 1:5:2, ball milling for 10 hours and drying to obtain dried powder;
[0052] Step 3. The dried powder obtained in step 2 is placed in a muffle furnace for pre-sintering at a temperature of 830° C. for 3 hours to form a powder of the main crystal phase of PZT;
[0053] Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT (near the morphotropic phase boundary MPB) at room temperature for 40 minutes, pass through 80-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder;
[0054] Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 5 MPa to pre-press and compact it to obtain a pre-pressed block;
[0055] Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -1 The target material is subjected to pressure sintering at a sintering temperature of 850°C, a holding pressure of 25 MPa, and a holding pressure sintering time of 8 min to obtain a semi-finished target material.
[0056] Step 7. Annealing the semi-finished target obtained in step 6, in an atmospheric environment, at an annealing temperature of 800° C., for 10 hours;
[0057] Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it with an automatic polishing machine; polish until the surface is smooth, wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; finally, dry it at 80°C for 6 hours.
[0058] Example 3
[0059] A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, specifically comprising the following steps:
[0060] Step 1. According to the chemical formula of the raw material components, the molar mass ratio is Pb3O4: ZrO2: TiO2 = 685.6: 60.3778: 40.7337, molecular formula: Pb(Zr 0.49 Ti 0.51 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder;
[0061] Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, the mass ratio of powder: anhydrous ethanol: grinding balls is 1:4:4, ball mill for 11 hours and dry to obtain dried powder;
[0062] Step 3. The dried powder obtained in step 2 is placed in a muffle furnace for pre-sintering at a temperature of 850° C. for 4 hours to form a powder of the main crystal phase of PZT;
[0063] Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT at room temperature for 50 minutes, pass through 70-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder;
[0064] Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 7Mpa to pre-press and compact it to obtain a pre-pressed block;
[0065] Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -2 The target material is subjected to pressure sintering at a temperature of 900°C, a holding pressure of 25 MPa, and a holding pressure sintering time of 15 min to obtain a semi-finished target material.
[0066] Step 7. Annealing the semi-finished target obtained in step 6 in an atmospheric environment at a temperature of 750° C. for 8 hours;
[0067] Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it with an automatic polishing machine; polish until the surface is smooth, wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; finally, dry it at 100°C for 3 hours.
[0068] The semi-finished target material processed in step 8 is connected to the target material back plate by using conductive adhesive to complete the preparation of the PZT target material.
[0069] Example 4
[0070] A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, specifically comprising the following steps:
[0071] Step 1. According to the chemical formula of the raw material components, the molar mass ratio is Pb3O4: ZrO2: TiO2 = 685.6: 62.8422: 39.1363, molecular formula: Pb(Zr 0.51 Ti 0.49 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder;
[0072] Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, with the mass ratio of powder: anhydrous ethanol: grinding balls being 1:3:3, and ball milling for 11 hours and drying to obtain dried powder;
[0073] Step 3. The dried powder obtained in step 2 is placed in a muffle furnace for pre-sintering at a temperature of 900° C. for 5 hours to form a powder of the main crystal phase of PZT;
[0074] Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT at room temperature for 50 minutes, pass through 60-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder;
[0075] Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 7Mpa to pre-press and compact it to obtain a pre-pressed block;
[0076] Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -2 The target material is subjected to pressure sintering at a temperature of 850°C, a holding pressure of 30 MPa, and a holding pressure sintering time of 14 min to obtain a semi-finished target material.
[0077] Step 7. Annealing the semi-finished target obtained in step 6 in an atmospheric environment at a temperature of 750° C. for 9 hours;
[0078] Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it using an automatic polishing machine; polish until the surface is smooth, wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; and finally dry it at 90°C for 3h.
[0079] The semi-finished target material processed in step 8 is connected to the target material back plate by using conductive adhesive to complete the preparation of the PZT target material.
[0080] Example 5
[0081] A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, specifically comprising the following steps:
[0082] Step 1. According to the molar mass ratio of the raw material components, Pb3O4: ZrO2: TiO2 = 685.6: 64.0744: 38.3376, molecular formula: Pb(Zr 0.52 Ti 0.48 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder;
[0083] Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, the mass ratio of powder: anhydrous ethanol: grinding balls is 1:5:3, ball mill for 9 hours and dry to obtain raw powder;
[0084] Step 3. Place the dried powder obtained in step 2 into a muffle furnace for pre-sintering at a temperature of 800° C. for 3 hours to form a powder of the main crystal phase of PZT;
[0085] Step 4. Grind the powder of the PZT main crystal phase (near the morphotropic phase boundary MPB) formed after pre-sintering in step 3 at room temperature for 30 minutes, pass through 60-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder;
[0086] Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 5 MPa to pre-press and compact it to obtain a pre-pressed block;
[0087] Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -1 The target material is subjected to pressure sintering at a sintering temperature of 850°C, a holding pressure of 20 MPa, and a holding pressure sintering time of 8 min to obtain a semi-finished target material;
[0088] Step 7. Annealing the semi-finished target obtained in step 6, in an atmospheric environment, at an annealing temperature of 800° C., for 10 hours;
[0089] Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it with an automatic polishing machine; polish until the surface is smooth, wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; finally, dry it at 80°C for 6 hours.
[0090] The semi-finished target material processed in step 8 is connected to the target material back plate using conductive adhesive to complete the preparation of the PZT target material.
[0091]
[0092] Table 1 shows the main process parameters and target material test data
[0093]
[0094] Table 2 compares the process parameters of traditional solid phase sintering and spark plasma sintering, and summarizes the main process parameters of the target material. Compared with other traditional solid phase sintering methods, the SPS spark plasma sintering method for preparing piezoelectric ceramic PZT target material has an SPS heating rate that is 10 times faster than muffle furnace heating, and the heating rate is significantly improved; and the sintering temperature is about 200 to 500°C lower than traditional solid phase sintering; it can achieve rapid densification of the material at a lower temperature, which helps to retain finer grains, thereby improving the performance of the material and greatly reducing energy consumption. It proves that the method of the present invention is fast, efficient, and has lower energy consumption. At the same time, the prepared target material has a high density and meets the requirements of high-performance piezoelectric devices. Figure 2 The XRD spectrum of the PZT target prepared by the present invention shows that there are no impurity peaks and no other impurity phases. Figure 6 From the SEM photograph of the PZT target prepared by the present invention, it can be seen that the grains of the target material of the present invention are relatively small as a whole, and the grains are not grown by rapid sintering.
Claims
1. A PZT target for magnetron sputtering, characterized in that: Its molecular formula is PbZr (0.48-0.52) Ti (0.48-0.52), and the molar mass ratio of the raw material components is Pb3O4: ZrO2: TiO2 = 685.6: (59.1456-64.0744): (38.3376-41.5324).
2. A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, characterized in that: The specific steps include: Step 1. According to the molar mass ratio of raw material components chemical formula Pb3O4: ZrO2:TiO2=685.6:(59.1456-64.0744):(38.3376-41.5324), take the raw materials and mix them evenly to obtain a mixed powder; Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, ball mill for 8 to 12 hours and dry to obtain dried powder; Step 3. Pre-sinter the dried powder obtained in step 2 at a temperature of 800 to 900° C. for 3 to 5 hours to form a powder of the main crystal phase of PZT; Step 4. Grind the powder of the PZT main crystal phase formed after pre-sintering in step 3 at room temperature for 10 to 60 minutes, pass through a 60 to 100 mesh sieve, and take the powder with a particle size of less than 0.150 mm as hot pressing powder; Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the sps device, apply a pressure of 5 to 10 MPa to pre-press and compact it to obtain a pre-pressed block; Step 6. Place the block obtained in step 5 in an SPS device for pressure sintering in a vacuum environment to obtain a semi-finished target material; Step 7. Annealing the semi-finished target material obtained in step 6; Step 8. Mechanically grind the surface of the semi-finished target material obtained after annealing in step 7, remove the surface carburized layer, and then polish it with an automatic polishing machine until the surface is smooth; wipe the polished target material with acetone to remove surface organic matter; then perform ultrasonic cleaning to remove impurities; finally, dry it at 80-120°C for 2-6 hours.
3. The method for preparing a PZT target for magnetron sputtering by spark plasma sintering according to claim 2, characterized in that: In step 2, the mass ratio of powder: anhydrous ethanol: grinding balls is 1: (2-5): (2-5).
4. The method for preparing a PZT target for magnetron sputtering by spark plasma sintering according to claim 2, characterized in that: The vacuum degree of the vacuum environment in step 6 is 5*(10 -2 ~10 -1 ), the sintering temperature of pressure sintering is 800-1000°C, the holding pressure is 20-30MPa, and the pressure holding sintering time is 8-15min.
5. The method for preparing a PZT target for magnetron sputtering by spark plasma sintering according to claim 2, characterized in that: The annealing treatment in step 7 is carried out in an atmospheric environment, with an annealing temperature of 700 to 900° C. and an annealing time of 8 to 10 hours.
6. The method for preparing a PZT target for magnetron sputtering by spark plasma sintering according to claim 2, characterized in that: The semi-finished target material processed in step 8 is connected to the target material back plate by using conductive adhesive to complete the preparation of the PZT target material.
7. A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, characterized in that The specific steps include: Step 1. According to the molar mass ratio of the raw material components chemical formula, Pb3O4: ZrO2:TiO2=685.6:59.1456:41.5324, molecular formula: Pb(Zr 0.48 Ti 0.52 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder; Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, with the mass ratio of powder: anhydrous ethanol: grinding balls being 1:3:2, and ball milling for 12 hours and drying to obtain dried powder; Step 3. Place the dried powder obtained in step 2 into a muffle furnace for pre-sintering at a temperature of 900° C. for 4 hours to form a powder of the main crystal phase of PZT; Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT at room temperature for 30 minutes, pass through 60-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder; Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 7Mpa to pre-press and compact it to obtain a pre-pressed block; Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -2 The target material is subjected to pressure sintering at a sintering temperature of 920°C, a holding pressure of 30 MPa, and a holding pressure sintering time of 10 min to obtain a semi-finished target material. Step 7. Annealing the semi-finished target obtained in step 6, in an atmospheric environment, at an annealing temperature of 700° C., for 8 hours; Step 8. The semi-finished target material obtained after annealing in step 7; mechanically grind the surface to remove the surface carburized layer, and then polish it with an automatic polishing machine; wipe the polished target material with acetone to remove surface organic matter, perform ultrasonic cleaning to remove impurities; and finally dry it at 100°C for 4 hours.
8. A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, characterized in that: The specific steps include: Step 1. According to the molar mass ratio of the raw material components chemical formula, Pb3O4: ZrO2:TiO2=685.6:61.61:39.935, molecular formula: Pb(Zr 0.5 Ti 0.5 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder; Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, the mass ratio of powder: anhydrous ethanol: grinding balls is 1:5:2, ball milling for 10 hours and drying to obtain dried powder; Step 3. The dried powder obtained in step 2 is placed in a muffle furnace for pre-sintering at a temperature of 830° C. for 3 hours to form a powder of the main crystal phase of PZT; Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT at room temperature for 40 minutes, pass through 80-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder; Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 5 MPa to pre-press and compact it to obtain a pre-pressed block; Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -1 The target material is subjected to pressure sintering at a sintering temperature of 850°C, a holding pressure of 25 MPa, and a holding pressure sintering time of 8 min to obtain a semi-finished target material. Step 7. Annealing the semi-finished target obtained in step 6, in an atmospheric environment, at an annealing temperature of 800° C., for 10 hours; Step 8. The semi-finished target material obtained after annealing in step 7; mechanically grind the surface to remove the surface carburized layer, and then polish it with an automatic polisher; wipe the polished target material with acetone to remove surface organic matter, perform ultrasonic cleaning to remove impurities; and finally dry it at 80°C for 6 hours.
9. A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, characterized in that: The specific steps include: Step 1. According to the molar mass ratio of the raw material components chemical formula, Pb3O4: ZrO2:TiO2=685.6:60.3778:40.7337, molecular formula: Pb(Zr 0.49 Ti 0.51 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder; Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, the mass ratio of powder: anhydrous ethanol: grinding balls is 1:4:4, ball mill for 11 hours and dry to obtain dried powder; Step 3. The dried powder obtained in step 2 is placed in a muffle furnace for pre-sintering at a temperature of 850° C. for 4 hours to form a powder of the main crystal phase of PZT; Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT at room temperature for 50 minutes, pass through 70-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder; Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 7Mpa to pre-press and compact it to obtain a pre-pressed block; Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -2 The target material is subjected to pressure sintering at a temperature of 900°C, a holding pressure of 25 MPa, and a holding pressure sintering time of 15 min to obtain a semi-finished target material. Step 7. Annealing the semi-finished target obtained in step 6 in an atmospheric environment at a temperature of 750° C. for 8 hours; Step 8. The semi-finished target material obtained after annealing in step 7; mechanically grind the surface to remove the surface carburized layer, and then polish it with an automatic polishing machine; wipe the polished target material with acetone to remove surface organic matter, perform ultrasonic cleaning to remove impurities; and finally dry it at 100°C for 3h.
10. A method for preparing a PZT target for magnetron sputtering by using a spark plasma sintering method, characterized in that: The specific steps include: Step 1. According to the molar mass ratio of the raw material components chemical formula, Pb3O4: ZrO2:TiO2=685.6:62.8422:39.1363, molecular formula: Pb(Zr 0.51 Ti 0.49 ) taking raw materials and uniformly mixing the raw materials to obtain a mixed powder; Step 2. Add anhydrous ethanol and grinding balls to the powder mixed in step 1, with the mass ratio of powder: anhydrous ethanol: grinding balls being 1:3:3, and ball milling for 11 hours and drying to obtain dried powder; Step 3. The dried powder obtained in step 2 is placed in a muffle furnace for pre-sintering at a temperature of 900° C. for 5 hours to form a powder of the main crystal phase of PZT; Step 4. Grind the powder formed by pre-sintering in step 3 to form the main crystal phase of PZT at room temperature for 50 minutes, pass through 60-mesh and 100-mesh sieves, and take the powder with a particle size of less than 0.150 mm as hot pressing powder; Step 5. Put the hot pressed powder obtained after sieving in step 4 into the assembled pre-pressing mold and place it in the SPS device, apply a pressure of 7Mpa to pre-press and compact it to obtain a pre-pressed block; Step 6. Place the block obtained in step 5 in a vacuum environment of the sps device with a vacuum degree of 5*10 -2 The target material is subjected to pressure sintering at a temperature of 850°C, a holding pressure of 30 MPa, and a holding pressure sintering time of 14 min to obtain a semi-finished target material. Step 7. Annealing the semi-finished target obtained in step 6 in an atmospheric environment at a temperature of 750° C. for 9 hours; Step 8. The semi-finished target material obtained after annealing in step 7; mechanically grind the surface to remove the surface carburized layer, and then polish it with an automatic polishing machine; wipe the polished target material with acetone to remove surface organic matter, perform ultrasonic cleaning to remove impurities; and finally dry it at 90°C for 3h.
Citation Information
Patent Citations
High-density PZT (Pb-based lanthanum doped Zirconate Titanate) target and preparation method thereof
CN107445617A